2016
DOI: 10.1159/000452616
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension and Adverse Outcomes in Prematurity: Comparing Definitions

Abstract: Background: In the premature neonate, there is no consensus regarding normal blood pressure (BP). The most common definition used is a mean arterial BP (MAP) less than the gestational age (GA); however, studies indicate that the neuroprotective mechanism of autoregulation is lost below a MAP of 30 mm Hg. Objective: To determine whether hypotension defined as MAP <30 mm Hg or MAP less than the infant's GA better predicts adverse outcomes of intraventricular hemorrhage (IVH) and death. Study Design: For this ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 37 publications
0
27
1
3
Order By: Relevance
“…It is unlikely that hypotension alone has definite causal effects on the severity of BPD because hypotension sometimes reflects multifactorial poor medical conditions. However, even apart from BPD, other studies have shown the significance of hypotension as a risk factor for mortality and adverse outcomes in VLBWIs [21]. For this reason, hypotension was not significantly different for the 24-week GA group in this study, since we excluded deaths before BPD diagnosis.…”
Section: Discussionmentioning
confidence: 70%
“…It is unlikely that hypotension alone has definite causal effects on the severity of BPD because hypotension sometimes reflects multifactorial poor medical conditions. However, even apart from BPD, other studies have shown the significance of hypotension as a risk factor for mortality and adverse outcomes in VLBWIs [21]. For this reason, hypotension was not significantly different for the 24-week GA group in this study, since we excluded deaths before BPD diagnosis.…”
Section: Discussionmentioning
confidence: 70%
“…Thirty-six percent of subjects were treated with dopamine, which is similar to what has been reported in the literature. 1,2,5 Infants treated with dopamine did not differ in demographic characteristics such as BW, GA, and sex from the neonates not exposed to dopamine. However, these subjects were significantly more likely to have a higher SNAPPE-II illness severity score, were exposed to high-frequency ventilation, had severe (grades 3 and 4) IVH, and have increased mortality, suggesting a higher acuity in this population.…”
Section: Discussionmentioning
confidence: 87%
“…Up to 50% of premature infants will be diagnosed with hypotension during the first 4 days of life, and of those up to half will be treated with vasopressor therapy. [1][2][3] Hypotension, although not well defined in this population, is known to be associated with increased morbidity (intraventricular hemorrhage (IVH) and neurologic impairments) and mortality, especially when requiring vasopressor therapy. [4][5][6][7][8] Dopamine is the most commonly used vasopressor in neonatal care because of its ability to effectively increase mean arterial pressure (MAP), but its effect on cerebral blood flow is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…This also supports our research. There is no consensus regarding normal blood pressure in premature neonates [26][27][28]; however, some studies indicate that the neuroprotective mechanism of autoregulation is lost below MAP of 30 mmHg [26]. For example, infants who developed severe IVH have been shown as having substantially more unstable MAP, and therefore, spent significantly more time with extreme MAP values (< 23 mmHg or > 46 mmHg) as compared with those without severe IVH [27].…”
Section: Discussionmentioning
confidence: 99%